Analyzing the barriers and enablers to internet hospital implementation: a qualitative study of a tertiary hospital using TDF and COM-B framework - Wu, Xiaolong; Kuang, Yulin; Guo, Yonglin; Wei, Ning; Fan, Zichun; Ling, Jingru (Frontiers in Digital Health, 2024)
BackgroundInternet hospitals have become an important way to improve the accessibility of medical services and promote medical equity in China. However, there is still lack of research on the behavior of medical personnel during the process of using Internet medical services, and the elements of behavior that motivate doctors to actively use or resist the use of Internet hospitals are still not fully analyzed. The study applied the Theoretical Domains Framework to examine the factors affecting the engagement of medical personnel in Internet hospitals, with the aim of guiding the design of intervention to enhance Internet hospital participation.MethodsThis study utilized qualitative analysis. Semi-structured questionnaires based on the Theoretical Domains Framework (TDF) and Capability-Opportunity-Motivation-Behavior (COM-B) model was developed and administered to 40 doctors and nurses at a Grade A tertiary hospital in Guangdong Province. Data was coded and analyzed using qualitative methods including Nvivo software.ResultsThe research displayed 19 barriers and 7 enablers for the implementation of Internet hospitals, all 14 TDF domains impacted participation with motivation cited most frequently. Despite challenges, medical personnel exhibited a generally optimistic stance towards utilization of the Internet hospital. Major barriers include the higher requirement of diagnostic ability, objective difficulties brought by online consultation to the decision-making process, limitation of time and other resources, not ideal technological and institutional environment, lack of self-efficacy and negative expectation of results in online consultation. Key enablers include patient needs and the positive impact of online care on the medical process and patient experience.DiscussionThis qualitative study identified a range of barriers and enablers to Internet hospital participation according to medical personnel, providing an conceptual framework to guide further research evaluating implementation strategies. Expanded research and targeted interventions design can help optimize participation in this evolving healthcare delivery model.